A cardiac magnetic resonance myocardial strain patterns analysis in left bundle branch block. (19th May 2022) - Santos, M; Silva, M; Guerreiro, S; Gomes, D; Rocha, B; Cunha, G; Freitas, P; Abecasis, J; Carmo, P; Cavaco, D; Morgado, F; Adragao, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Recently, a classification with four types of septal longitudinal strain patterns was described using a speckle tracking based strain analysis in echocardiography suggesting pathophysiological continuum of LBBB-induced LV remodeling. Little data exist on feature tracking cardiac magnetic resonance (FT-CMR) in LBBB patients, and whether such patterns could be reproduced in CMR is not established yet. Purpose: In this study, we aimed to: 1) Assess and reproduce the new strain patterns classification by CMR and 2) Evaluate its association with LV remodeling and myocardial scar in a LBBB cohort. Methods: Single center registry which included LBBB patients with septal flash (SF) referred to CMR to assess the structural cause of LV dysfunction. LBBB was defined according to Strauss criteria as strict LBBB, non-strict LBBB or nonspecific LV conduction delay. A semi-automated FT-CMR was used to quantify myocardial strain and detect the four septal longitudinal and radial strain patterns, according to the recent classification (LBBB-1 through LBBB-4) – Figure. Extent of SF was visually scored as mild, moderate, or prominent. Results: A total of 115 patients were included (mean age 66±11 years; 57% men; 38% with ischemic heart disease). Median duration of QRS was 150± 26ms and majority of the patients (n=90, 78%) were classified as strict LBBB. In longitudinal strain analyses LBBB-1 was observed in 23 (20%), LBBB-2 in 37 (32.1%), LBBB-3 in 25 (21.7%), and LBBB-4 in 30 (26%) patients. Patients at higher LBBB stages (longitudinal or radial pattern) had more prominent septal flash, greater LV volumes, lower LV ejection fraction and lower absolute global longitudinal, circumferential and radial strain values compared with patients in less advanced stages (p < 0.05 for all) - table. There was no difference between patterns in clinical characteristics, ischemic etiology, QRS duration and time delay between septal and lateral LV wall. Late gadolinium enhancement (LGE) was found in 63 patients (54.8%), with a septal location in 34 (29.6%) patients, lateral in 4 (3.5%) patients, septal and lateral in 11 (9.6%) patients. Furthermore, no difference was found for LGE presence, distribution or location between the four strain patterns. Conclusions: Among patients with LBBB, our study found a good association between longitudinal and radial strain patterns with the degree of LV remodeling and LV dysfunction by FT-CMR analysis. Additionally, myocardial fibrosis didn't seem to interfere with the staged LBBB classification.